2021
DOI: 10.1051/0004-6361/202140674
|View full text |Cite
|
Sign up to set email alerts
|

Molecular gas and star formation within 12 strong galactic bars observed with IRAM-30 m

Abstract: Context. While some galactic bars show recent massive star formation (SF) along them, some others do not. Whether bars with low level of SF are a consequence of low star formation efficiency, low gas inflow rate, or dynamical effects remains a matter of debate. Aims. In order to study the physical conditions that enable or prevent SF, we perform a multi-wavelength analysis of 12 strongly barred galaxies with total stellar masses log10(M⋆/M⊙)∈[10.2, 11], chosen to host different degrees of SF along the bar majo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 198 publications
(251 reference statements)
1
10
3
Order By: Relevance
“…In barred galaxies, the radial dependence is not monotonic because R 21 is elevated around bar ends, where star formation is active (Muraoka et al 2016;Maeda et al 2020;Koda et al 2020). Díaz-García et al (2021) did not find a clear correlation between R 21 and SFR, but it is at least partially due to different beam sizes and thus to a possible overestimation of the intrinsic ratio. In addition to the variation within a galaxy, R 21 differs among galaxies.…”
Section: Introductionmentioning
confidence: 71%
“…In barred galaxies, the radial dependence is not monotonic because R 21 is elevated around bar ends, where star formation is active (Muraoka et al 2016;Maeda et al 2020;Koda et al 2020). Díaz-García et al (2021) did not find a clear correlation between R 21 and SFR, but it is at least partially due to different beam sizes and thus to a possible overestimation of the intrinsic ratio. In addition to the variation within a galaxy, R 21 differs among galaxies.…”
Section: Introductionmentioning
confidence: 71%
“…In contrast to the studies that have observed individual barred galaxies, as detailed above, recent statistical studies have suggested that the SFE in the bars is not systematically lower than that in other regions, and that it is, in fact, environmentally independent (e.g., Muraoka et al 2019;Díaz-García et al 2021;Querejeta et al 2021). Muraoka et al (2019) measured the radial variations in the SFEs of 80 galaxies (30 SA, 33 SAB, and 17 SB galaxies) selected from the CO Multi-line Imaging of Nearby Galaxies (COMING) project (Sorai et al 2019).…”
Section: Introductionmentioning
confidence: 75%
“…The authors define the bar parameters by using Spitzer 3.6 μm images. For the galaxies outside the catalog, when available, we adopt the values reported in the literature that were calculated based on near-IR images (Kuno et al 2007;Menendez-Delmestre et al 2007;Díaz-García et al 2021). For galaxies that did not have any corresponding literature, we visually ascertain whether R bar is larger than 37 5; however, no galaxies are visually selected.…”
Section: Nearby Face-on Barred Galaxies With An Apparent Longbar Stru...mentioning
confidence: 99%
“…Barred galaxies may have shorter depletion timescales measured for the whole galaxy (e.g., Géron et al 2021). Still, a recent spatially resolved study found no remarkable differences in the Kennicutt-Schmidt law in the central regions of barred and unbarred galaxies (Díaz-García et al 2021). Strongly barred galaxies do not necessarily have enhanced central star formation rates (SFRs; Wang et al 2012Wang et al , 2020Consolandi et al 2017;Díaz-García et al 2020).…”
Section: Introductionmentioning
confidence: 99%